IgG4 related disease (IgG4-RD) as a costochondral mass: A rare presentation - Ajoy Oommen John; Ajay Kumar Mishra; Anne Jennifer; Ronald Albert Benton Carey (Wolters Kluwer Medknow Publications, 2018)
A 39-year-old female came for evaluation for progressive lower costochondral pain and swelling with no associated systemic or constitutional symptoms and no evidence of the involvement of any other organ system. Diagnostic thoracotomy with excision of involved rib and costochondral junction showed plasma cell-rich chronic inflammation with foci of fibrosis with no definite storiform fibrosis or obliterative phlebitis. Immunohistochemistry showed 30%-40% immunoglobulin G4 (IgG4)-positive cells/hpf with an IgG:IgG4 ratio of 30% with sterile cultures and no elevation of serum IgG4 levels. With a presumptive diagnosis of IgG4-related disease, she was started on steroids with which she had complete symptom relief and resolution of the lesion. This case highlights the importance of considering the diagnosis of IgG4 disease even in the absence of typical histopathological findings and elevated serum IgG4 levels. The authors have not found any prior reports in the English literature of IgG4 disease of the ribs and costochondral junction.